Copeptin as a Diagnostic and Prognostic Biomarker in Cardiovascular Diseases - Mu, Danni; Cheng, Jin; Qiu, Ling; Cheng, Xinqi (Frontiers in Cardiovascular Medicine, 2022)
Copeptin is the carboxyl-terminus of arginine vasopressin (AVP) precursor peptide. The main physiological functions of AVP are fluid and osmotic balance, cardiovascular homeostasis, and regulation of endocrine stress response. Copeptin, which is released in an equimolar mode with AVP from the neurohypophysis, has emerged as a stable and simple-to-measure surrogate marker of AVP and has displayed enormous potential in clinical practice. Cardiovascular disease (CVD) is currently recognized as a primary threat to the health of the population worldwide and thus rapid and effective approaches to identify individuals that are at high risk of, or have already developed CVD is required. Copeptin is a diagnostic and prognostic biomarker in CVD, including the rapid rule-out of acute myocardial infarction (AMI), mortality prediction in heart failure (HF), and stroke. This review summarizes and discusses the value of copeptin in the diagnosis, discrimination, and prognosis of CVD (AMI, HF, and stroke), as well as the caveats and prospects for the application of this potential biomarker.